New cytotoxic indole derivatives with anti-FADU potential produced by the endophytic fungus Penicillium oxalicum 2021CDF-3 through the OSMAC strategy - Song, Wei; Ji, Lianlian; Zhang, Yanxia; Cao, Longhe (Frontiers in Microbiology, 2024)
Fungi possess well-developed secondary metabolism pathways that are worthy of in-depth exploration. The One Strain Many Compounds (OSMAC) strategy is a useful method for exploring chemically diverse secondary metabolites. In this study, continued chemical investigations of the marine red algae-derived endophytic fungus Penicillium oxalicum 2021CDF-3 cultured in PDB media yielded six structurally diverse indole derivatives, including two new prenylated indole alkaloids asperinamide B (1) and peniochroloid B (5), as well as four related derivatives (compounds 2-4 and 6). The chemical structures of these compounds, including the absolute configurations of 1 and 5, were determined by extensive analyses of HRESIMS, 1D and 2D NMR spectroscopic data, and TDDFT-ECD calculations. Compound 1 was found to possess an unusual 3-pyrrolidone dimethylbenzopyran fused to the bicyclo[2.2.2]diazaoctane moiety, which was rare in previously reported prenylated indole alkaloids. In vitro cytotoxic experiments against four human tumor cell lines (HeLa, HepG2, FADU, and A549) indicated that 1 strongly inhibited the FADU cell line, with an IC 50 value of 0.43 ± 0.03 μM. This study suggested that the new prenylated indole alkaloid 1 is a potential lead compound for anti-FADU drugs.